Efter det kritiske subjekt - Bolt, Mikkel (K&K - Kultur og Klasse, 2024)
The article revisits the question of the critical subject through a reading of Jacques Rancière and Fred Moten. It starts out by giving an account of a longer historical trajectory where the notions of critique and revolution have run into the ground. David Scott’s nuanced analysis of the shift from an anticolonial romantic revolutionary perspective to a tragic postcolonial stance is both affirmed and challenged. Affirmed in so far as Scott’s analysis is embedded in a broader historical context, challenged by the presentation of two attempts to think the notion of a critical subject after the disappearance of a previous notion of an antisystemic subject. The second half of the article is a discussion of Rancière’s notion of a political subjectivation that is not based on pre-existing identities but is a break with the logic of a functionalist society. Followed by a discussion of Moten’s concept of Blackness that follows the Afro-Pessimist reading of the radical dispossession of Blacks but turn it into a possibility for a different kind of community.